Rocky [videorecording (Blu-Ray)] - Avildsen, John G., 1935-2017; Stallone, Sylvester; Shire, Talia; Young, Burt; Weathers, Carl; David, Thayer, 1927-1978; Meredith, Burgess, 1907-1997 (Twentieth Century Fox Home Entertainment, 2014)
Rocky Balboa, a club fighter seemingly going nowhere, gets his once-in-a-lifetime opportunity to go the distance and come out a winner when fate puts him in the ring with the world heavyweight champion.